Meningkatkan Hasil Belajar Siswa melalui Penerapan Problem-Based Learning pada Mata Pelajaran Biologi: Meningkatkan Hasil Belajar Siswa melalui Penerapan Problem-Based Learning pada Mata Pelajaran Biologi - Pana, Irawaty Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
Improving the quality of learning is an important factor that supports the achievement of progress in the field of education. In order to improve the quality of learning, it is necessary to apply innovative learning that follows the student-oriented learning paradigm. This study aims to describe the application of the Problem-based Learning Model by utilizing the environment as a learning resource to improve learning outcomes in biology. This classroom action research consisting of 2 research cycles and each cycle consists of four stages: (1) planning; (2) implementing actions; (3) observation and evaluation; (4) reflection. The study was conducted at Model 5 High School Palu. The subject of this research is Class X MIPA with 28 students. In this study the focus of learning material on biodiversity. The instruments used were student worksheets, student and teacher activity sheets, and student learning outcomes tests. The research data were displayed as a percentage and analyzed descriptively. The learning outcomes of Class X Science 6 of SMA Negeri 5 Palu can be improved through the application of PBL learning models through the use of the environment. In cycle 1 students 'classical completeness was 71.66, while students' classical completeness in cycle 2 increased by 88.09. The classical absorption achieved in cycle 1 was 62.16%, increasing to 91.89% in cycle 2.